Implementasi Keamanan Jaringan Berbasis VPN dan Anti - DDoS dalam Melindungi Server Linux dari Serangan Hammer: Array - Pangestu, Raka Nugraha; Yanti, Risma; Harahap, Herlina (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
Although there are many security methods that can be used to block DDoS attacks, for now these methods are arguably less effective, because many hackers have known bugs from the system or security methods. From the background of this problem, testing the security of Linux Mint servers, Linux Mint without VPN and Anti DDoS, implementing network security from hammer attacks on Linux Mint Linux servers with VPN and Anti-DDoS, and testing DDoS and VPN attacks have been successfully implemented. on linux mint. Anti-DDoS and VPN are able to prevent DDoS attacks on Linux servers by blocking unknown IPs from accessing the server and redirecting attacks to virtual IPs provided by the VPN.